FACTORS INFLUENCING GREEN BUILDING DEVELOPMENT IN KAZAKHSTAN - Assylbekov, Daniyar (Nazarbayev University School of Engineering and Digital Sciences, 2021)
Green building has been actively spreading as a solution for sustainability issues in the construction industry of the last decades. As green building practices unfold in developing countries, the necessity of identifying factors that both hinder and drive its spread rises. Multiple studies reveal general inconsistency among results in different parts of the world, caused by environmental, economic, and social conditions of the country. Considering international green building development experience and the current state of development of green building in Kazakhstan, this study aims to spread our understanding upon the factors that obstruct and have the potential to drive green building development in Kazakhstan. A questionnaire survey was carried out among 38 industry experts in Kazakhstan to accomplish study objectives. Multiple data analysis methods were used to identify correlations among groups of experts and rank the factors. The results revealed a lack of skilled/experienced, lack of government support, and high cost of sustainable materials and products to be the most crucial barriers. Water- and energy-efficiency, and improved occupants' health, comfort, and satisfaction were identified to be the most influential drivers. By expanding knowledge about factors affecting the implementation of green building, the study uncovered common trends in the professionals' responses, providing valuable information for the field practitioners and suggesting future research recommendations.
Keywords: green building; Type of access: Open Access; Research Subject Categories::TECHNOLOGY; energy-efficiency; green building technology; GBT